2014
DOI: 10.1371/journal.pone.0113662
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptional Evidence for the Role of Chronic Venlafaxine Treatment in Neurotrophic Signaling and Neuroplasticity Including also Glutatmatergic- and Insulin-Mediated Neuronal Processes

Abstract: ObjectivesVenlafaxine (VLX), a serotonine-noradrenaline reuptake inhibitor, is one of the most commonly used antidepressant drugs in clinical practice for the treatment of major depressive disorder (MDD). Despite being more potent than its predecessors, similarly to them, the therapeutical effect of VLX is visible only 3–4 weeks after the beginning of treatment. Furthermore, recent papers show that antidepressants, including also VLX, enhance the motor recovery after stroke even in non depressed persons. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 107 publications
1
33
0
Order By: Relevance
“…Previously published data have shown that venlafaxine is linked to increased mRNA expression of MMP‐9 in the rat brain (Tamasi et al . ). With respect to the potential to disrupt PV to pyramidal cell input, which would likely have a profound influence on widespread population activity, MMP‐9 has also been shown to diminish PNN integrity (Murase et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previously published data have shown that venlafaxine is linked to increased mRNA expression of MMP‐9 in the rat brain (Tamasi et al . ). With respect to the potential to disrupt PV to pyramidal cell input, which would likely have a profound influence on widespread population activity, MMP‐9 has also been shown to diminish PNN integrity (Murase et al .…”
Section: Resultsmentioning
confidence: 97%
“…Consistent with this possibility is work demonstrating increased MMP‐9 expression in venlafaxine‐treated rats (Tamasi et al . ). While effects of specific monoamines on MMP release from brain‐derived cells have not been extensively studied, in non‐neural cells, norepinephrine has been shown to enhance MMP expression as well as MMP‐dependent endpoints (Yang et al .…”
mentioning
confidence: 97%
“…Further, ZDHHC7 palmitoylates sex steroid hormone receptors affecting the rapid intracellular signaling by sex hormones via ERK and AKT kinases [149]; sex steroid hormones are known to modulate synaptic plasticity [150], mood, and antidepressant response [151]. GRIN2B (glutamate receptor ionotropic N-methyl D-aspartate 2) is a known member of the long-term potentiation pathway (as reported above), and the expression of this gene is modulated by venlafaxine together with neurotrophic and neuroplasticity genes [152].…”
Section: Neuronal Plasticitymentioning
confidence: 94%
“…Studies have shown that venlafaxine prevented chronic stress-induced decreased hippocampal cell proliferation (Feng et al, 2012) and the reduction in NMDA receptor 2B expression (Tamasi et al, 2014;Yilmaz et al, 2011). However, the mechanisms whereby venlafaxine affects DISC1 and its partner PDE4B remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%